Bone marrow evaluation in a pediatric population with pancytopenia in a tertiary care children’s hospital of Nepal - Uma Bhatta; Sagar Rana Magar; Surendra Khanal (Journal of Pathology of Nepal)
Background: Pancytopenia, which is characterized by a triad of anemia, leukopenia, and thrombocytopenia, is frequently observed among the pediatric population. This study was carried out to determine the common etiologies of pancytopenia in children through bone marrow aspiration examination.